Deteksi Dini Obesitas melalui Pemeriskaan Komposisi Tubuh pada Populasi Usia Produktif di SMAN 75, Jakarta Utara - Ruslim, Daniel; Destra, Edwin; Gunaidi, Farell Christian; Fadhila, Arni Ismi (BADAN PENERBIT STIEPARI PRESS, 2024)
Body composition, which consists of the proportion of fat, bone, water and muscle, is very important for adolescent health. Adolescence is characterized by significant changes in body composition that are influenced by genetics, hormones, physical activity, and nutrition. Bioelectrical impedance analysis (BIA), a non-invasive and cost-effective method, is widely used to assess body composition, including fat mass and fat-free mass. Excess body fat in adolescence is associated with cardiovascular disease, type 2 diabetes, and obesity. This activity uses the PDCA (Plan-Do-Check-Action) methodology, which involves the facial skin analysis of 163 participants. According to the examination results, the average total body fat, total subcutaneous fat, visceral fat, and total muscle mass were 24.9%, 21%, 2.5%, and 27.5%, respectively. Early assessment and intervention are essential to prevent health complications. Promoting healthy lifestyles and regularly monitoring body composition can improve adolescent health and prevent future obesity-related morbidity and mortality.